Employer size, productivity, labour quality, working conditions, internal labour markets and wages: an empirical analysis of the hotel industry in Andalusia - Alejandro García-Pozo; Andrés J. Marchante-Mera; José Luis Sánchez-Ollero; José López-Rubio; Carlos G. Benavides-Chicón (European Regional Science Association (ERSA), 2012)
In this paper, the diversity of job characteristics and wage gaps in the Spanish hotel industry due to different employer size have been studied. A labour market in which wages depend on employer size means the characteristics of the same job differs between firms. In the hotel industry the data indicate significant differences in the nature of the job according to the size of the establishment. This topic has been analysed for many economic sectors but, as far as we know, not for the hotel industry. Using data from the research project "Mismatch in education, productivity and wages in the Andalusian tourism sector", the first aim was to establish whether there was a similar positive relationship between employer size and wages in the hotel industry. The second aim was to account for wage premia earned by workers employed by larger hotels taking into account the specific characteristics of each establishment. The results have shown that even after controlling for the workers' observable characteristics and the other determinants of our wage equation, a substantial wage differential remained between large and small establishments. To achieve these aims four hypotheses on productivity, labour quality, working conditions and internal labour markets was tested. Based on adding the productivity measure, the results show that this variable accounts for 17.8% of the establishment-size wage premium. Similar results were obtained when adding our own measures of working conditions. However, the size-wage relationship remains almost unaffected when controlling for labour quality and internal labour market variables. It is also possible that large establishments pay higher wages simply because they employ workers with more unobserved abilities. To take into account the workers' unobserved heterogeneity, we need to specify a model that allows for the potential self-selection by workers of hotels of various sizes, and this is a task that cannot be achieved with the available data. However, bearing in mind that different explanatory hypotheses of wage differences between different size hotels have different implications for the management of human resources, identifying the sources of the wage-establishment size effect is a relevant question for future research.
Keywords: J31; L83; R23; 330; Hotel industry; employer size; segmented labour markets; wage gaps; productivity and working conditions